Development In Figures: Human Development Index of Tabalong Regency 2010-2024 - Baseran Nor; Suratno Martodiryo; Alfi Fadhilah Hakim Harahap; Tania Azzahra Salsa Bella; Halimah Halimah (International Journal of Multidisciplinary Sciences and Arts, 2026)
The Human Development Index (HDI) serves as a vital instrument for assessing regional progress by integrating health, education, and living standards. As a strategic buffer zone for Indonesia’s future capital, Tabalong Regency’s pursuit of enhanced human development is of particular importance. This study analyzes the longitudinal evolution of Tabalong’s HDI from 2010 to 2024, quantifies the relative contributions of its core components, and proposes evidence-based policy interventions. Employing a quantitative approach with time-series and cross-sectional data from official statistics, the analysis employs multiple linear regression and t-tests. The findings indicate that Tabalong maintains the third-highest HDI in South Kalimantan, driven overwhelmingly by per capita expenditure (99.6% contribution), with education indicators as secondary contributors, while life expectancy exhibits a markedly weaker influence. Statistical tests confirm significant differences in all component means between regencies with medium and high HDI. The discussion contextualizes these results within contemporary scholarship on regional development and inequality. The study concludes by advocating for an integrated policy framework emphasizing strengthened community health services, equitable and quality education, environmentally conscious pedagogy, and economic diversification through agricultural productivity, MSME empowerment, and sustainable tourism. These measures are essential for fostering inclusive and resilient human development in alignment with national strategic planning.